Problem-based learning on trigonometry topic: Independent curriculum teaching module - Wati, Linda; Yerizon, Yerizon (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Students often struggle to understand trigonometry. In this context, problem-based learning emerges as an innovative approach that can enhance students' problem-solving abilities through contextual problem-solving. Therefore, the development of an independent curriculum teaching module based on PBL is necessary to improve the quality of learning.Aim: The aim of this research is to develop a valid independent curriculum teaching module based on problem-based learning for trigonometry topics.Method: This research employs the Plomp development model to create the trigonometry teaching module. The module was validated by five experts, consisting of three mathematics experts, one language expert, and one graphic design expert. Validation was conducted using a pre-tested validation sheet. The validation results were analyzed and averaged to determine their alignment with validity criteria.Result: Based on the validation results, it was found that the developed teaching module as a whole achieved an average score of 3.63, meeting the very valid criteria for each assessed aspect.Conclusion: The independent curriculum teaching module based on problem-based learning for trigonometry topics is valid for use in mathematics education. This research indicates that the module can enhance the quality of learning and students' mathematical problem-solving skills. Future studies are recommended to test the effectiveness of this module in a broader context and with students of varying ability levels.